Analisis Pengaruh Faktor Pribadi dan Budaya Terhadap Keputusan Pembelian - Nina Herlina; Yuyun Susanti; Asep Edwin Ramadhan (Jurnal Inovasi Bisnis dan Kewirausahaan, 2021)
Abstract– This study aims to determine: 1) The magnitude of the influence of personal factors on purchasing decisions at Alfamart Batukaras; 2) The magnitude of the influence of cultural factors on purchasing decisions at Alfamart Batukaras; 3) The magnitude of the influence of personal and cultural factors on purchasing decisions at Alfamart Batukaras. The research method used in this study is an explanatory survey research method with a quantitative data approach. The number of population that will be used as the object of research is the number of consumers of Alfamart Batukaras in December 2019 as many as 1,698 people. The sample size selected was 94 people. Data collection techniques in this research are library research, field studies (observations, interviews and questionnaires). Based on the results of the study that: 1) There is a positive and significant influence on personal factors on consumer purchasing decisions at Alfamart Batukaras. This means that if personal factors increase then consumer purchasing decisions will increase; 2) There is a positive and significant influence of cultural factors on consumer purchasing decisions at Alfamart Batukaras. This means that if cultural factors increase, consumer purchasing decisions will increase, 3) There is a positive and significant influence of personal and cultural factors on consumer purchasing decisions at Alfamart Batukaras. This means that if personal factors and cultural factors increase then consumer purchasing decisions will increase. Abstrak– Penelitian ini bertujuan untuk mengetahui: 1) Besarnya pengaruh faktor pribadi terhadap keputusan pembelian pada Alfamart Batukaras; 2) Besarnya pengaruh faktor budaya terhadap keputusan pembelian pada Alfamart Batukaras; 3) Besarnya pengaruh faktor pribadi dan faktor budaya terhadap keputusan pembelian pada Alfamart Batukaras. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian survey explanatory dengan pendekatan data kuantitatif. Jumlah populasi yang akan dijadikan objek penelitian adalah jumlah konsumen Alfamart Batukaras pada bulan Desember 2019 yaitu sebanyak 1.698 orang. Ukuran sampel yang dipilih adalah sebanyak 94 orang. Teknik pengumpulan data dalam penelitian ini adalah studi kepustakaan, studi lapangan (observasi, wawancara dan angket). Berdasarkan hasil penelitian bahwa : 1) Terdapat pengaruh yang positif dan signifikan faktor pribadi terhadap keputusan pembelian konsumen pada Alfamart Batukaras. Artinya jika faktor pribadi meningkat maka keputusan pembelian konsumen akan meningkat; 2) Terdapat pengaruh yang positif dan signifikan faktor budaya terhadap keputusan pembelian konsumen pada Alfamart Batukaras. Artinya jika faktor budaya meningkat maka keputusan pembelian konsumen akan meningkat, 3) Terdapat pengaruh yang positif dan signifikan faktor pribadi dan faktor budaya terhadap keputusan pembelian konsumen pada Alfamart Batukaras. Artinya jika faktor pribadi dan faktor budaya meningkat maka keputusan pembelian konsumen akan meningkat.